2023
DOI: 10.1039/d2cc05169a
|View full text |Cite
|
Sign up to set email alerts
|

Structural origins of two-dimensional elastic bending in a nonaromatic organic molecular crystal

Abstract: A two-dimensional elastically bent crystal based on hydrogen bonding in a nonaromatic organic molecule system was reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The expansion of the unit cell ensuing from the photodimerization generates stress, leading to bending of the acicular crystals of PMA-I away from the light. According to the Euler–Bernoulli equation 47 , 48 , thick crystals with larger thickness will experience more strain when reaching the same radius of curvature, which, since they cannot bend, can concentrate at defects and result in crystal explosion. This has already been demonstrated on photosalient crystals undergoing linkage isomerization 49 as well as with thermally induced disintegrative effects, known as the thermosalient effect 11 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expansion of the unit cell ensuing from the photodimerization generates stress, leading to bending of the acicular crystals of PMA-I away from the light. According to the Euler–Bernoulli equation 47 , 48 , thick crystals with larger thickness will experience more strain when reaching the same radius of curvature, which, since they cannot bend, can concentrate at defects and result in crystal explosion. This has already been demonstrated on photosalient crystals undergoing linkage isomerization 49 as well as with thermally induced disintegrative effects, known as the thermosalient effect 11 .…”
Section: Resultsmentioning
confidence: 99%
“…11a ). However, when the strain exceeds 0.7% (calculated based on the Euler–Bernoulli equation ε n = ( t /2 R ) 47 , 48 , where t is the thickness and R is the radius of curvature), an irreversible plastic deformation occurs. Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…29,30 Several recent studies reported unusual plastic crystals based on strong hydrogen bonding. 31,32 Strong hydrogen bonding was also found to play a nonnegligible role in elastic crystals of isosorbide 5-mononitrate 33 and (2S,3R)-3ethyl-1-phenylhex-5ene-2,3-diol. 34 The methodologies based on hydrogen bonding are still far more useful and general compared to those based on halogen bonding, π−π interactions, etc.…”
Section: Introductionmentioning
confidence: 97%
“…These soft molecular crystals share properties of both crystals and soft matter, endowing them with great potential in mechanical actuators, optical devices, organic electronics, etc. The mechanical properties of molecular crystals strongly rely on the molecular packing arrangements and intermolecular interactions, which can be tailored by crystal engineering approaches. Designing new structures with the desired physical and chemical properties using advanced third-generation strategies of crystal engineering is an attractive and rapidly developing research area. , Much effort has been made to study the mechanism of flexible crystals and gain a deep understanding of mechanical compliance to a large extent. The importance of weak dispersive interactions has been acknowledged as it has a natural advantage in controlling local molecular movements, which is essential to ensure the effective dissipation of stresses generated from structural functions. Almost all of the key structures of mechanically flexible crystals exhibit a combination of weak intermolecular interactions such as van der Waals (vdW), weak hydrogen-bonding, , lighter halogen, ,, and π···π interactions. , Several recent studies reported unusual plastic crystals based on strong hydrogen bonding. , Strong hydrogen bonding was also found to play a nonnegligible role in elastic crystals of isosorbide 5-mononitrate and (2 S ,3 R )-3-ethyl-1-phenylhex-5ene-2,3-diol . The methodologies based on hydrogen bonding are still far more useful and general compared to those based on halogen bonding, π–π interactions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Although many mechanically soft molecular crystals are known today, 10–29 the rational design 30,31 of such systems still remains a formidable challenge. Many unanswered questions still remain.…”
Section: Introductionmentioning
confidence: 99%